The Effect of Adding Protected Amino Acids in the Rumen (Methionine and Lysine and their Mixtures) on Some Physiological Characteristics of Male Arabi Lambs - Yahya Harbi Abdul-Noor; Amad Falah Hassan (مجلة ديالى للعلوم الزراعية, 2021)
This study was conducted at the animal field of the Agriculture College / University of Basra / Karma Ali site for the period from 7/10/2019 to 1/5/2020 to investigation the effect of adding protected amino acids (methionine and lysine and their mixtures) on some physiological trails of male Arabi lambs. Sixteen male lambs with an average weight of (27.95) kg and an age of 5-6 months were selected, and randomly divided into four group (4 animals per group). The results indicated that there were no significant differences in the concentration of hemoglobin, packed cell volume, the number of red and white blood cells, cholesterol, triglycerides and the activity of the liver enzyme (ALT and AST) between the different treatments, while there was a significant (p <0.05) increase in the total protein and albumin concentration in the fourth treatment compared with the first treatment (control), while, there was a significant decrease (p <0.05) in the urea concentration for the fourth, third and second treatments compared with the first treatment. The concentrations of glucose, thyroxine and growth hormone increased significantly (p <0.05) in the fourth and second treatment compared with the first treatment. However, it can be concluded from the study that feeding the male lambs with 5g methionine or mixing it with lysine by 5g raises the concentration of glucose, growth hormones and thyroxine in the blood. Also, the levels of methionine and lysine used did not change the concentration of the studied biochemical parameters.